“Straight out of the button-molder’s own ladle”: On the complexity of characters in Arthur Koestler’s Thieves in the Night - Vernyik, Zénó (International Journal of English Studies, 2016)
This paper discusses the complexity of female and Arab characters in Arthur Koestler’s Thieves in the Night. Through an analysis of three main characters (Dina, Ellen and the Mukhtar of Kfar Tabiyeh) and several minor ones, it shows that the allegation of contemporary reviews, and some works on Arthur Koestler ever since, that the novel is excessively built on stock characters is untenable. In fact, the representation of women and Arabs is both specific and detailed, in addition to the fact that these characters show a clearly detectable line of development, even if their initial presentation might in some cases be reminiscent of Petrarchan or other types.